Dedicated operating room for emergency surgery improves access and efficiency - Heng, Marilyn (Canadian Medical Association, 2013)
BACKGROUND: Scheduling emergency cases among elective surgeries often results in prolonged waits for emergency surgery and delays or cancellation of elective cases. We evaluated the benefits of a dedicated operating room (OR) for emergency procedures available to all surgical services at a large children’s hospital. METHODS: We compared a 6-month period (January 2009 to June 2009) preimplementation with a 6-month period (January 2010 to June 2010) postimplementation of a dedicated OR. We evaluated OR use, wait times, percentage of cases done within and outside of access targets, off-hours surgery, cancellations, overruns and length of stay. RESULTS: Preimplementation, 1069 of the 5500 surgeries performed were emergency cases. Postimplementation, 1084 of the 5358 surgeries performed were emergency cases. Overall use of the dedicated OR was 53% (standard deviation 25%) postimplementation. Excluding outliers, the average wait time for priority 3 emergency patients decreased from 11 hours 8 minutes to 10 hours 5 minutes (p = 0.004). An increased proportion of priority 3 patients, from 52% to 58%, received surgery within 12 hours (p = 0.020). There was a 9% decrease in the proportion of priority 3 cases completed during the evening and night (p < 0.001). The elective surgical schedule benefited from the dedicated OR, with a significant decrease in cancellations (1.5% v. 0.7%, p < 0.001) and an accumulated decrease of 5211 minutes in overrun minutes in elective rooms. The average hospital stay after emergency surgery decreased from 16.0 days to 14.7 days (p = 0.12) following implementation of the dedicated OR. CONCLUSION: A dedicated OR for emergency cases improved quality of care by decreasing cancellations and overruns in elective rooms and increasing the proportion of priority 3 patients who accessed care within the targeted time.